THE NEW FORMATION OF THE PUBLIC SERVANT IN NORTH KALIMANTAN PROVINCE (STUDI :THE RECRUITMENT OF THE NEW STATE OFFICERS IN NORTH KALIMANTAN ) - Raudah Mahmud (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2017)
The aim of this research is to know the reason why the  local Government of North Kalimantan Province to recruit the new officer.Recruitment is the process to look for , find , ask to join and ditermine a few persons from insider or outsider of the company as the candidates of the manpower with the special characteristics as being defined in the planning of the the human resources.  The results of the recruitment process is the the sum manpower who will take the selction process namely the one to ditermine the candidte who is the best to fulfil the certain position in the company concerned ((Schuer & Jakson,1996:232).The method of it is qualitative and by library one.The location is in the local Government , North Kalimantan Province .The results are (1). The local Government ,North Kalimantan Province, as a new province needs  new officers ,(2).There will be recruitment by test ,(3).The candidates have to prepare seriously to compete.The suggestions are (1).The young as the candidates have to prepare to take the recruitment test by studying hard.(2).The local government in regencies and municipal have to guide the candidates as well as possible.